Folk Healing Narratives: A Grounded Theory - Maria Cristal Nual Velez (Journal of English Education and Linguistics, 2021)
This study collected, transcribed, translated, and categorized the folk healing narratives from Magarao, Camarines Sur to reveal the shared meanings and derived a theory about them. The researcher used descriptive method to describe the existing folk healing narratives and contact method was used in gathering the data then followed the process of Grounded Theory Method. The collected narratives from the nine (9) folk healers were classified into four (4) categories namely; pagbulong sa paagi kan gabay (healing through the help of supernatural being), pagbulong sa paagi kan ritwal (healing through rituals), pagbulong sa paagi kan pagsanib (healing through possession), and pagbulong sa paagi kan namanang kaaraman (healing through acquired knowledge). From the categories of folk healing narratives, the researcher extracted the shared meanings that resulted to the four (4) stages of folk healing: pag-apod (calling), pag-isi (knowing), pag-umay (healing), and pag-arang (offering). This study concluded that for folk healers to perform folk healing, they combine their skills and gift of healing that was endowed to them by the Supreme Being. The extracted shared meanings reflect how people who adhere to folk healing view the world; this is because of their similarities in experiences. Shared meanings which are present in these modern times can be traced back from the practices and beliefs of the ancient Bikolanos reflected in the Bikol literature. This study recommends the future researchers to conduct similar studies specifically in the shared meanings and practices in the other aspects of the society